Satisfacción de los usuarios de servicios postales de la Empresa Pública Correos del Ecuador en la ciudad de Loja, primer trimestre del 2019 - León Pullaguari, Luis David (2019)
This research called “Satisfaction of postal service users of the Public Company Correos del Ecuador in the city of Loja, first quarter of 2019”, will determine the level of satisfaction that the entity's external users have in the Branch located in the city of Loja, established in legal instruments such as the Constitution of the Republic, the National Development Plan and other regulations that guarantee the quality of public services, supported by a theoretical framework with concepts directly related to the subject matter and a framework referential that knows the entity. The present investigation to establish the target population determined a monthly average of users who approach the customer service offices to do some procedure or consultation, this information is obtained thanks to the daily records provided by the entity obtaining a sample of 298 users which were surveyed using the SERVQUAL model and Likert scale that measured the dimensions and their respective related to the quality of service and user satisfaction, contrasting their expectations and perceptions before and after receiving the service. Once the results were tabulated, the main results were obtained highlighting a global gap of -0.55 between the perceptions and expectations of the surveyed users, which determined a service that does not meet the needs of the users, the entity's strength being the dimension of empathy that presented the most favorable results.